2021
DOI: 10.1177/10406387211064270
|View full text |Cite
|
Sign up to set email alerts
|

Fatal infection with Versteria sp. in a muskrat, with implications for human health

Abstract: The Taeniidae tapeworms are a family of helminths that have a similar life cycle, with intermediate hosts developing characteristic cysts in visceral organs. We describe here a case in Pennsylvania, USA, of fatal Versteria infection in a muskrat ( Ondatra zibethicus), which, to our knowledge, has not been reported to develop disease associated with infection. Postmortem examination revealed widespread tissue loss and replacement by solid-bodied cestode larvae with minimal adjacent inflammation in many visceral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Recently, Niedringhaus et al (2021) reported a fatal infection by cysticerci of Versteria sp. in a muskrat Ondatra zibethicus (L.) in Pennsylvania, USA; remarkably, in the same locality where a case of human cysticercosis was reported ( Lehman et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Niedringhaus et al (2021) reported a fatal infection by cysticerci of Versteria sp. in a muskrat Ondatra zibethicus (L.) in Pennsylvania, USA; remarkably, in the same locality where a case of human cysticercosis was reported ( Lehman et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was integrated into the clade which also included Versteria sp. from the orangutan and from humans ( Niedringhaus et al, 2021 ). Unfortunately, the sequence of Versteria sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations